Utilization of Colocynth (Handal) Seeds Oil as a Lubricating Base Oil - Abdelrahman, Maha A. A.; Yassin, Atif A. A.; Abdou, Abdelnasir M. (Gezira Journal of Engineering and Applied Sciences; Vol 7 No 1 (2012), 2018)
This study investigated the use of Colocynth seeds oil as lubricating base oil. The Colocynth seeds were collected from Eastern Gezira and Western Kordofan. Viscosity index is 162 and 164; Flash point is 292 o C and 288 o C for Eastern Gezira and Western Kordofan samples, respectively. The pour point is -3 o C for both samples. At 40 o C, the kinematics viscosity is 34.37 cSt and 32.69 cSt, and at 100 o C is 8.00 cSt and 7.77 cSt for Eastern Gezira and Western Kordofan samples, respectively. The study suggested that the Colocynth seeds oil is a suitable base fluid to produce lubricants .